Dissipative Particle Dynamic Simulation of Oil-Water Two-Phase Flow in Quartz Slits - Jiuzhu Wu; Jiaqi Li (Geofluids)
Aiming to study the characteristics and mechanism of oil-water two-phase flow, based on the method of dissipative particle dynamics (DPD), meso-scale models of pressure-driven flow in quartz slits with width of 5-15 nm were simulated. Water is the driving phase. The results show that, as the liquid flew, it stratified gradually. The stratification came earlier as the width, and the driving force increased. The flow in slit of 5 nm was slug flow, while velocity profiles in other models showed parabolic characteristics. When the liquid stratified, the velocity gradient in the near-wall area decreased as a result of the low momentum exchange rate between from water to oil. The density peaks of fluid appeared at the fluid-solid interface and the oil-water interface, caused by the fluid-solid interaction force and the oil-water repulsion, respectively. The oil phase showed stronger aggregation due to the attractive force from the wall. When the water saturation was 25%, the water phase was a water droplet surrounded by oil. When the water saturation was 75%, oil and water stratified. As the repulsive force between the two phases decreased, the surface tension decreased, the mixing degree increased, and the parabolic characteristics of the velocity profile were more obvious.